Peran Harga dan Kualitas dalam Keputusan Konsumen Memilih Gula Curah sebagai Produk Ekonomis di Pasar Tradisional - Futri Medwina Siregar; Vista Uli Sihombing (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Traditional markets remain the main centers for meeting community food needs, including the purchase of bulk sugar, which is widely recognized as an economical product. This study aims to analyze the role of price and quality in shaping consumers’ decisions to purchase bulk sugar at Tavip Traditional Market, Binjai City. The research employed a quantitative approach using a survey method involving 70 bulk sugar consumers. Data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The results of the measurement model evaluation indicate that all variables meet the criteria of validity and reliability. Furthermore, the structural model results show that price and quality have a significant effect on purchase decisions. Price has a more dominant role than quality, indicating that affordability and price fairness are the main considerations for traditional market consumers when purchasing bulk sugar. Nevertheless, product quality remains an important supporting factor that strengthens consumer confidence in the purchasing decision-making process.